Pengaruh Work Life Balance, Quality Work Life dan Work Engagement terhadap Kinerja Pegawai Puskesmas Janti - Cyntya Anggreani Setyawan; Nurhidayah Nurhidayah; Mohammad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Puskesmas is an institution under the auspices of the Health Service which aims to organize health efforts that are comprehensive, integrated, equitable, acceptable and affordable for the people of Indonesia. However, we often see cases of bad health worker service practices at the Puskesmas. This study aims to determine the effect of work life balance, quality work life and work engagement on the performance of Janti Health Center employees. In this study using explanatory research with a quantitative approach. The population in this study were 34 health workers. Methods of data collection using a questionnaire. While the method of data analysis using instrument test, classical assumption test, multiple linear regression test and hypothesis testing. The results showed that work life balance and quality work life did not significantly influence the performance of Janti Health Center employees. Meanwhile, work engagement has a significant effect on the performance of Janti Health Center employees. Keywords: Work Life Balance, Quality Work Life, Work Engagement, Performance